Institutional Convergence - Aurel Iancu (Romanian Academy, National Institute for Economic Research, 2009)
In this chapter, we describe the essence and role of the institutions in the modern economic systems, the main issues concerning the institutional convergence in relation to the EU integration, the institutional capital and the impact of the quality and effectiveness of the institutions on filling the economic gap between countries, in the context of the implementation of the European integration strategy. * Study within the CEEX Programme Project No. 220/2006 Economic Convergence and Role of Knowledge in Relation to the EU Integration .
Keywords: E02; F36; F55; F59; O43; 330; Rules; formal institutions; informal institutions; transaction cost; integration; acquis; compliance; institutional capital; regression